Smart healthcare information system pharmacy management system / Leow Weng Yuen - Leow, Weng Yuen (2001)
This document covers 3 main areas in outlining the intended system in question; that is the Pharmacy Management System. The first section of this document is basically an introduction to the system. It covers the objective of the said system as well as the scope and area that it would cover. It also explains briefly its interaction and integration with other components being developed by 4 other course mates in the team. The Pharmacy Management System is a part of a larger system that we have dubbed as the "Smart Healthcare Information System". The second section covers an in-depth study of the tools that will be used to develop the system. This part of the document will contain an analysis as well as summaries of the various tools that have been looked at. It contains technical details as well as some conclusions that have been reached after studying the specifications of the various tools. Most of the information gleaned for this section was taken off various Internet articles as well as some books that are related to the project being proposed. The third section suggests the methodology that will be used to develop and test the system. The system design as well as the process taken to develop the system is covered in the later sections. This whole report caps everything off with screenshots and short captions to explain the final system that was developed.